Analysis of the Level of Service Satisfaction of BPJS Patients at the Primary Outpatient Clinic of UIN North Sumatra Using the Servqual Method - Syahfitri, Dewi; Pulungan, Dea Rizka Ananda; Gurning, Fitriani Pramita (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
Service quality is closely related to customer satisfaction because service quality can create a good relationship with the company and tell the company how to meet consumer needs. This study aims to determine the level of patient satisfaction with the services provided by the Primary Outpatient Clinic of UIN North Sumatra. The method in this study uses a quantitative approach, and the research design is carried out in a cross-sectional manner. The research sample of 50 respondents was selected through the purposive sampling method in accordance with the criteria of patients who received BPJS and had reading and writing skills. The results showed that all dimensions of SERVQUAL had a positive gap, with responsiveness as the highest dimension (0.49), followed by tangibles (0.36), assurance (0.35), reliability (0.32), and empathy (0.31). The CSI value of 82.61% indicates that patient satisfaction is in the very satisfied category. The conclusion of this study shows that the level of satisfaction of BPJS patients with the services at the Primary Outpatient Clinic of UIN North Sumatra is in the category of very satisfied. The responsiveness and tangibles dimensions received the highest ratings, while the empathy and a dimensions still needed improvement to be able to meet patient expectations more optimally and sustainably.